Peranan Penting Kitchen dalam Operasional The Windsor Hotel Toya Vignette Collection - Afisa Febria; Julian Andriani Putri (Mahesa Research Center, 2026)
This article aims to analyse the role of the kitchen department in supporting overall hotel operations at The Windsor Hotel Toya – Vignette Collection. The problem focuses on the kitchen’s contribution to service quality, operational efficiency, interdepartmental coordination, and guest satisfaction. The study applies service quality and hospitality operations management theories. Data were collected through in-depth interviews, observation, and documentation, and analysed qualitatively. The findings show that the kitchen acts as a quality control centre through standardised procedures, structured food safety practices, and systematic coordination. Efficiency is achieved through clear task distribution and inventory control. The kitchen also strengthens the hotel’s identity through local ingredients and service planning involvement. The study concludes that effective kitchen management is essential for maintaining service quality and hotel image. The implication suggests that strengthening kitchen management systems can enhance competitiveness and operational sustainability.